Molecular detection and species identification of Enterocytozoon bieneusi isolated from immunocompetent Orang Asli in Malaysia. Issue 2 (April 2017) - Ashikin, Azah; Al-Mekhlafi, Hesham M.; Moktar, Norhayati; Anuar, Tengku Shahrul
Abstract: Most studies of opportunistic infections focus on immunocompromised patients. However, there is a lack of information on microsporidiosis in healthy people (immunocompetent) worldwide. This study aimed to detect and identify microsporidia species in immunocompetent Orang Asli living in Pahang, Malaysia. Orang Asli is a collective term for a group of indigenous people that usually reside in the interior regions of Peninsular Malaysia. They comprise about 0.7% of the total population in Malaysia and 76% of them lived below the poverty line i.e., poor housing conditions with the lack of access to safe drinking water and adequate sanitation, contaminated environment, high illiteracy rate and unhygienic practices by these people. Stool samples were collected from 209 Orang Asli and analyzed for detecting the presence of Enterocytozoon bieneusi and Encephalitozoon intestinalis by polymerase chain reaction assay targeting small subunit ribosomal RNA gene. E. bieneusi was detected in 8 individuals (3.83%). This infection was commonly found in males than females (5.2% vs. 2.7%). All infected Orang Asli were adults, with a mean age of 44 years. Diarrhea and other gastrointestinal symptoms were reported in one case (12.5%) among individuals infected with this species. These findings clearly show that exposure to E. bieneusi may actually be common than reported. The accurate detection and identification of microsporidian species by molecular technique will improve therapy, clinical manifestations and prognosis of this infection, as no antiparasitic therapy has been approved for E. bieneusi . It is hoped that these findings will allow the formulation of better health management and disease prevention advisories, and improvement in the standards of health in similar communities. Graphical abstract: Highlights: This study is the first report on E. bieneusi presence in immunocompetent Orang Asli in Malaysia. SSU rRNA of E. bieneusi was detected in 8/209 (3.83%) Orang Asli with a mean age of 44 years. Diarrhea and fever were only reported in one (12.5%) Orang Asli infected with this species.